Greater Cortical Thickness in Elderly Female Yoga Practitioners—A Cross-Sectional Study - Afonso, Rui F.; Balardin, Joana B.; Lazar, Sara; Sato, João R.; Igarashi, Nadja; Santaella, Danilo F.; Lacerda, Shirley S.; Amaro Jr., Edson; Kozasa, Elisa H. (Frontiers in Aging Neuroscience, 2017)
Yoga, a mind-body activity that requires attentional engagement, has been associated with positive changes in brain structure and function, especially in areas related to awareness, attention, executive functions and memory. Normal aging, on the other hand, has also been associated with structural and functional brain changes, but these generally involve decreased cognitive functions. The aim of this cross-sectional study was to compare brain cortical thickness in elderly yoga practitioners and a group of age-matched healthy non-practitioners. We tested 21 older women who had practiced hatha yoga for at least eight years and 21 women naive to yoga, meditation or any mind-body interventions who were matched to the first group in age, years of formal education and physical activity level. A T1-weighted MPRAGE sequence was acquired for each participant. Yoga practitioners showed significantly greater cortical thickness in a left prefrontal lobe cluster, which included portions of the lateral middle frontal gyrus, anterior superior frontal gyrus and dorsal superior frontal gyrus. We found greater cortical thickness in the left prefrontal cortex of healthy elderly women who trained yoga for a minimum of eight years compared with women in the control group.